The glass hotel [compact disc, unabridged] - Mandel, Emily St. John, 1979- (Random House Audio, an imprint of the Penguin Random House Audio Publishing Group, 2020)
Vincent is a bartender at the Hotel Caiette, a five-star glass and cedar palace on an island in British Columbia. Jonathan Alkaitis works in finance and owns the hotel. When he passes Vincent his card with a tip, it's the beginning of their life together. That same day, Vincent's half-brother, Paul, scrawls a note on the windowed wall of the hotel: 'Why don't you swallow broken glass.' Leon Prevant, a shipping executive for a company called Neptune-Avramidis, sees the note from the hotel bar and is shaken to his core. Thirteen years later Vincent mysteriously disappears from the deck of a Neptune-Avramidis ship. Weaving together the lives of these characters, the story moves between the ship, the skyscrapers of Manhattan, and the wilderness of northern Vancouver Island, painting a breathtaking picture of greed and guilt, fantasy and delusion, art and the ghosts of the pasts.